Does Governance Transparency Lead to More Supportive Foreign Investment? - Luan, Chin-Jung; Jiang, Hong-Yi; Tien, Chengli (Journal of Asian Business Strategy, 2016)
This paper attempts to delineate the relationship between a firm’s information transparency and disclosure (T&D), by which it can attract more investment from FII (foreign institutional investors), and its associated performance impacted by FII investment. Employing a unique data set of ranking reports of transparency and disclosure of listed firms of Taiwan and the financial databank of the Taiwan Economic Journal, the results of the study show that the stronger the intent of a firm’s voluntary disclosure concerning corporate governance, the more shares that FII will hold, which can lead to better performance for the invested firms, suggesting that FII provides resources not only to guard their investments but also to improve firm performance. Beyond regulatory requirement of disclosure, firms should strategize their efforts in disclosing governance information voluntarily; these efforts can generate external resources infusion, and the resources can help improve firm performance.